ANALISIS MANAJEMEN DATA KESEHATAN DI DOKTER PRAKTEK MANDIRI KECAMATAN SENDANG AGUNG KABUPATEN LAMPUNG TENGAH TAHUN 2023 - Syahroni, Arfan; Riyanti, Riyanti (Journal of Hospital Administration and Excellent Health Service, 2024)
Introduction:Independent practice doctors are one of the goals for patients to get health services. In practice, before a patient comes to an independent doctor's practice, the patient has already decided whether to go to a general practitioner or a specialist. Doctors who practice independently in their services obtain data and information from the patients themselves. The data obtained is in the form of health data and identity data from the patient. related to the health data obtained, whether the independent doctor's practice has collaborated with the nearest health service facility and how health data management is carried out. This research discusses Health Data Management Analysis at Independent Practicing Doctors, Sendang Agung District, Central Lampung Regency. Method: Qualitative research using triangulation techniques using observation, interviews and documentation methods. The research was conducted at the independent practice of Dr. Siti Nur Indah, Sendang Mulyo Village, Sendang Agung District, Central Lampung Regency. There were 3 contributors to this research information. Results: the data produced at Dr. Siti Nur Indah's independent medical practice in the Central Lampung area is complete, this is shown in the registration book and patient medical records. Everything is recorded appropriately and completely. The completeness of the data available is still manual-based, meaning that the data recorded only uses paper without any digitization or use of supporting applications, so in this case there is still the potential for files to be difficult to find and lost. Apart from that, the data has not been reported to the nearest health service facility, this is evidenced by the lack of cooperation between private medical practices and community health centers, but regarding diseases that have the potential for outbreaks and treatment needs to be carried out at the community health center level, independent practicing doctors directly coordinate with the nearest community health center staff. , this is proven by WhatsApp messages sent to community health center officers regarding patients who need further treatment. Conclusion: Independent medical practice at dr. Siti Nur Indah's data management is good, complete and stored appropriately. However, the implementation is still done manually without using computer applications and devices. Apart from that, the health data obtained has not been made into graphic tables or carried out further analysis to determine disease trends and health status in the community. Apart from that, there has also been no reporting to the nearest health center regarding health data.